Edukasi Tentang Risiko Obat Tradisional Tanpa Izin Edar Bagi Kesehatan Ibu Hamil - Djunaedi, Djunaedi; Putri, Maidina (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The use of traditional medicines remains a primary choice among the public because they are considered natural, inexpensive, and readily available. However, not all traditional medicines are safe, especially for pregnant women, as some lack distribution permits from the Food and Drug Monitoring Agency (BPOM), which carries the risk of containing hazardous materials, non-standardized dosages, or being contaminated with chemical substances (ZKO). This community service activity aims to increase the knowledge of pregnant women and their families regarding the risks of using traditional medicines without distribution permits. The methods used were health education through lectures, interactive discussions, and leaflet distribution. The results of the activity showed an increase in participants' understanding of the dangers of using traditional medicines without distribution permits and the importance of medical consultation before taking medication during pregnancy. It is hoped that this activity will reduce the risky use of traditional medicines and raise awareness of the importance of drug safety for maternal and fetal health.